Rebuilding Lives: The Effectiveness of REBT Counseling in Improving the Psychological Well-being of Adolescents from Broken Home Backgrounds - Lestari, Erna Puji; Sa’diyah, Khansa Nabilatus; Bariyyah, Khairul; Jami’iyah, Jami’iyah (Universitas Negeri Malang, 2024)
Adolescents from broken homes often face various psychological problems such as anxiety, depression, and low self-esteem. Therefore, effective interventions are needed to help improve the psychological well-being of these adolescents. This study aims to evaluate the effectiveness of counseling with the Rational Emotive Behavior Therapy (REBT) approach in improving the psychological well-being scores of 10th-grade high school students in Malang Regency who come from broken homes. The treatment process was conducted based on REBT counseling procedures, including the stages of A (Activating Event), B (Beliefs), C (Consequence), D (Dispute), E (Effect), F (New Feeling), and G (Goals). The research method used was an experiment with a single subject research design, A-B-A. The sample of the study consisted of students from broken homes with moderate psychological well-being. The research instrument used was the psychological well-being scale. Data were analyzed using visual graphical techniques. The results showed that REBT counseling increased the students' psychological well-being. Baseline A(1) was measured three times before the intervention (B) with an average score of 103. After the intervention, the scores increased to 133, 144, 153, and 153. Each aspect of psychological well-being also showed score increases. Irrational thoughts about self and family became more rational after treatment using empirical and logical disputing, thereby increasing the psychological well-being scores. Thus, it can be concluded that REBT counseling is effective in improving the psychological well-being scores of students from broken homes. Keywords: broken home; REBT counseling; psychological well-being; adolescents